(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The article aims to propose an analysis of the fictional narrative that traces the power relationship between Queen Elizabeth II and Prime Minister Margareth Thatcher, in the American series “The Crown”, Netflix’s original. Considering the relevance of visual media for the construction of memories, we intend to understand the reinterpretation of historical scenes in the logic of consumption.